2017
DOI: 10.1007/s10495-017-1349-3
|View full text |Cite
|
Sign up to set email alerts
|

Propofol attenuates H2O2-induced oxidative stress and apoptosis via the mitochondria- and ER-medicated pathways in neonatal rat cardiomyocytes

Abstract: Previous studies have shown that propofol, an intravenous anesthetic commonly used in clinical practice, protects the myocardium from injury. Mitochondria- and endoplasmic reticulum (ER)-mediated oxidative stress and apoptosis are two important signaling pathways involved in myocardial injury and protection. The present study aimed to test the hypothesis that propofol could exert a cardio-protective effect via the above two pathways. Cultured neonatal rat cardiomyocytes were treated with culture medium (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…All protocols in this study were approved by the Ethics Committee of Southwest Medical University. Neonatal rats (2–3 days) was used for the isolation and culture of neonatal rat cardiomyocytes (NRCMs) as we reported previously ( 14 ). Cultured NRCMs in DMEM with 10% FBS were further divided into four groups by different treatments: i) Control group: normal DMEM adding with 10% FBS, ii) H 2 O 2 group [with H 2 O 2 for 6 h at 500 µM ( 15 )], iii) DEX group [with DEX at 5 µM ( 16 )], and iv) H 2 O 2 + DEX group (with 5 µM DEX for 2 h before exposing to 500 µM H 2 O 2 for 6 h).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All protocols in this study were approved by the Ethics Committee of Southwest Medical University. Neonatal rats (2–3 days) was used for the isolation and culture of neonatal rat cardiomyocytes (NRCMs) as we reported previously ( 14 ). Cultured NRCMs in DMEM with 10% FBS were further divided into four groups by different treatments: i) Control group: normal DMEM adding with 10% FBS, ii) H 2 O 2 group [with H 2 O 2 for 6 h at 500 µM ( 15 )], iii) DEX group [with DEX at 5 µM ( 16 )], and iv) H 2 O 2 + DEX group (with 5 µM DEX for 2 h before exposing to 500 µM H 2 O 2 for 6 h).…”
Section: Methodsmentioning
confidence: 99%
“…ELISA was used in this study to detect the levels of lactic dehydrogenase (LDH), glutathione (GSH) and the activities of caspase 3, 8, 9 and 12 with ELISA kits according to the instructions and our previous research ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A key beginning event in the initiation of UPR is the dissociation of GRP78 from the three transmembrane sensor proteins, freeing them to activate distinct UPR pathways. In most examples of ER stress and UPR signaling, GRP78 is upregulated and UPR signaling is stimulated [ 29 , 30 ]. However, as seen in Figure 6 C, levels of GRP78 are reduced in the 3-month-old TauTKO heart, an effect associated with inhibition of UPR signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ), a highly reactive oxygen species (ROS), gives rise to wide spread oxidative damage, and has been widely used to mimic oxidative stress in vitro 7 . Previous studies have demonstrated that H 2 O 2 may also activate apoptosis in vivo 8 . The mitochondria-mediated intrinsic pathway and the cell death receptors-mediated extrinsic pathway are the main pathways involved in cell apoptosis 9 .…”
Section: Introductionmentioning
confidence: 97%